2002
DOI: 10.1042/0264-6021:3610621
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid activation of the ERK pathway is required for embryonic stem cell commitment into the adipocyte lineage

Abstract: Mouse embryonic stem (ES) cells are pluripotent cells that differentiate into multiple cell lineages. The commitment of ES cells into the adipocyte lineage is dependent on an early 3-day treatment with all-trans retinoic acid (RA). To characterize the molecular mechanisms underlying this process, we examined the contribution of the extracellular-signal-regulated kinase (ERK) pathway. Treatment of ES cell-derived embryoid bodies with RA resulted in a prolonged activation of the ERK pathway, but not the c-Jun N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(60 citation statements)
references
References 46 publications
(13 reference statements)
1
59
0
Order By: Relevance
“…Under these conditions large clusters of mature adipocytes are present in 70 to 80% of the embryoid bodies. Our laboratory has investigated the role of the ERK pathway during ES cell commitment into the adipocyte lineage [17]. We showed that retinoic acid activates the ERK pathway, and not the other MAPK pathways, in embryoid bodies during early events of adipocyte differentiation.…”
Section: The Erk Pathway In Adipogenesis: the Model Of Embryonic Stemmentioning
confidence: 99%
“…Under these conditions large clusters of mature adipocytes are present in 70 to 80% of the embryoid bodies. Our laboratory has investigated the role of the ERK pathway during ES cell commitment into the adipocyte lineage [17]. We showed that retinoic acid activates the ERK pathway, and not the other MAPK pathways, in embryoid bodies during early events of adipocyte differentiation.…”
Section: The Erk Pathway In Adipogenesis: the Model Of Embryonic Stemmentioning
confidence: 99%
“…Furthermore, major cell signaling pathways have been shown to mediate some of the effects of RA in ES and human cancer cells (Frédéric et al, 2002; Pettersson et al, 2004; Kogai et al, 2008; reviewed by Niles, 2004). Our antibody microarray analyses indicated that cells treated with a combination of RA plus AC expressed members of the p38/MAPK and PI3K/AKT pathways in a differential manner as compared to cells treated with RA only, which suggests their involvement on the induction of ES to endodermal differentiation by RARβ2.…”
Section: Discussionmentioning
confidence: 99%
“…PD98059, a selective inhibitor of the mitogen-activated protein kinase kinase (MAPKK/MEK) in the MAPK pathway 55 , inhibits at RA-induced MAPK activation 56 and cell differentiation 57 . In addition, MAPK activation increases the expression of the Raldh2 58 gene that encodes the enzyme responsible for the conversion of RAL to at RA and therefore, PD98059 can inhibit MAPK-induced at RA biosynthesis 59 .…”
Section: Discussionmentioning
confidence: 99%